THE EFFECTS OF TEACHING TECHNIQUE AND VOCABULARY MASTERY TOWARDS STUDENT’S SPEAKING SKILL - Abdul Kodir Al-Baekani (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2015)
The aim of this research is to know if there are effects of teaching technique and vocabulary mastery towards student’s speaking skill at State Senior High Schools in Karawang West Java. The population of this research is all the state senior high school students in Karawang. Meanwhile, the sample of this research is 60 students from two schools taken randomly. This research is quasi experimental design research with two factors; teaching technique using guessing song and conventional technique and vocabulary mastery. The data about vocabulary mastery and speaking skill are taken through tests. It has tested the validity and reliability test. The data analysis, the researcher used SPSS (Statistical Product and Service Solution) Program version 17,00. The result of data descriptive analysis in experimental class (A1) has mean score 77,83, it is more than in control class (A2) that has a mean score 68,83. Thedescription shows that the experimental class is successful. Testing of three hypothesis used ANOVA (analisis on varians), it has gotten the sig score  sig= 0,00 in guessing song teaching technique and vocabulary mastery. Therefore, the interaction guessing song teaching technique and vocabulary mastery got sig= 0,213, it means that the first hypothesis; there is significant effect of guessing song teaching technique towards student’s speaking skill is accepted. The second hypothesis; there is significant effect of vocabulary mastery towards student’s speaking skill is also accepted, while the third hypothesis; there are the effects of teaching technique using guessing song and vocabulary mastery towards student’s speaking skill is rejected.Keyword: Teaching Technique, Vocabulary Mastery, Speaking Skill.